Pengaruh Kompetensi dan Independensi Terhadap Kinerja Auditor - Dewi Anggraeni; Nur Aisyah; Hasrah; Nur Fatwa Basar (Jurnal Online Manajemen ELPEI, 2023)
This study aims to determine the effect of auditor competence and independence on auditor performance. This research was conducted at the Inspectorate Office of Gowa Regency. The type of data used in this research is quantitative data. The data sources used in this research are primary and secondary data. The analytical method used is descriptive statistical analysis and multiple linear regression. The population in this study amounted to 35 while the sample in this study amounted to 30. The results of this study indicate that competence has a positive and significant effect on auditor performance. While independence has a positive but not significant effect on auditor performance